1972
DOI: 10.1088/0022-3727/5/4/329
|View full text |Cite
|
Sign up to set email alerts
|

The determination of the optical constants of thin films from measurements of reflectance and transmittance at normal incidence

Abstract: The derivation of the components n and k of the complex refractive index of a thin film from measurements, at normal incidence, of reflectance R and transmittance T is complicated by the existence of multiple solutions of the relevant equations. It is shown that, although use of Tomlin's expressions for (1 ± R)/T rather than Heavens's explicit formulae for R and T separately simplifies the problem, it is still necessary to consider very carefully the multiple solutions. A procedure is given for determining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

1972
1972
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(49 citation statements)
references
References 6 publications
2
43
0
1
Order By: Relevance
“…The large band gap and transparency shown by the crystals make them a possible choice for optoelectronic application [39,46]. The transmittance (T) is given by the relation [47]:…”
Section: Optical Transmittance and Absorption Studiesmentioning
confidence: 99%
“…The large band gap and transparency shown by the crystals make them a possible choice for optoelectronic application [39,46]. The transmittance (T) is given by the relation [47]:…”
Section: Optical Transmittance and Absorption Studiesmentioning
confidence: 99%
“…In order to determine n and k for each single wavelength we substituted the measured thickness d of the film and the value s = 1.45 for the s refractive index of the substrate in the equation system (4) is the existence of (n, k) multiple solutions for singular values of T exp , R exp and d. Furthermore, at some specific wavelengths n(λ)and k(λ) curves exhibit discontinuities which are typical for the method of normal incidence transmittance and reflectance [27,31]. To restict the possibility of multiple solutions we solved the equation system (3)-(4) in the region 2.5-3.5 for n and in the region 0-1.5 for k .…”
Section: Resultsmentioning
confidence: 99%
“…If this was riot done it was found that closure of the dispersion curve (see Denton, Campbell, and Tomlin 1972) could not be achieved owing to insufficient Uniformity of film thickness. The substrate temperature could be maintained at any desired temperature between room temperature and 700°C.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It has been shown by Denton, Campbell, and Tomlin (1972) that the calculations are much simplified by using expressions for (1 ±R)/T rather than those for Rand T, and that the correct choice from the multiple solutions can be made unambiguously, together with an accurate determination of film thickness, provided measurements are made over a sufficiently wide range of wavelengths. The same paper also discusses the application of rigorous formulae, for a double layer film, to the investigation of thin surface layers and shows how to allow for the effects of such layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation